Edukasi Optimalisasi Bisnis UMKM: Inovasi dan Pendekatan Stratejik - Devi Marlita; Esti Liana; Erni Pratiwi Perwitasari; Sinai Handayani; Agus Suhendra; Sri Handayani; Lis Lesmini (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the national economy but face various challenges, such as limited innovation, market access, and less-than-optimal business strategies. This community service activity aims to increase the capacity of MSME players through education regarding business optimization with innovative and strategic approaches. The methods used include training, mentoring, and implementing simple technology to increase the competitiveness of MSMEs. The main focus of education includes product development, digital marketing, financial management, and adaptation strategies to market changes. It is hoped that the results of this activity will increase the understanding and skills of MSME players in managing their businesses more effectively and sustainably. With this education, MSMEs can be better prepared to face business challenges, increase productivity, and expand their market reach.